PENDIDIKAN ISLAM DI ERA GLOBALISASI: TANTANGAN MODERNITAS DAN PENGUATAN NILAI KEISLAMAN - Hidayat, Muhammad Fajar; Rosdiana; Damopolii, Muljono; Usman, Syahruddin (Al-Mumtaz: Jurnal Manajemen Pendidikan Islam, 2026)
Globalization and modernity have brought significant changes to many aspects of life, including Islamic education. The rapid flow of information, technological advancements, and cultural exchanges present both challenges and opportunities for Islamic education to remain relevant amid global changes. This paper aims to review the impact of globalization and modernization on Islamic education at various levels, assess modernization measures in Islamic education that can be implemented without neglecting the core principles of Islamic teachings, and analyze the contributions of educators, educational institutions, and society in improving the quality of Islamic education in this global and modern era. This study uses a qualitative method with a literature study approach through critical analysis of books, academic journal articles, and relevant documents from the last five years. Research results show that the phenomenon of globalization requires Islamic education to make adjustments through curriculum changes, the application of technology, and the development of 21st-century skills, while still adhering to Islamic principles such as ethics, spirituality, and balance. The modernization of Islamic education should not be understood as a process of following Western methods, but as a selective change aimed at strengthening Islamic identity. Therefore, collaboration between educators, educational institutions, and the community is very important in creating flexible, high-quality Islamic education that can compete at an international level without neglecting the core values of Islam.